Functional interaction between immune checkpoints and lipid metabolism in the development of arteriosclerosis obliterans - Zhang, Junyi; Cui, Liyuan; Meng, Xinhang; Luo, Yujie; Ou, Jingmin; Wang, Songcun; Qiu, Mingke (Frontiers in Immunology, 2025)
Arteriosclerosis obliterans (ASO) is a chronic vascular disease characterized by narrowing or occlusion of the vascular lumen. Its pathogenesis is complex and closely associated with lipid metabolism disorders and chronic inflammation. Although notable progress has been made in the treatment of ASO, it still remains a cause of surgical limb loss globally. In recent years, immune checkpoints have been identified as critical regulators of the immune microenvironment that play a significant role in ASO. Furthermore, immune checkpoints can affect lipid metabolism by regulating the metabolic pathways of immune cells, thereby indirectly modulating lipid metabolic processes, such as lipid absorption, transport, and degradation, which are crucial in the development and progression of atherosclerosis. Here, we summarized and discussed progress in studies related to lipid metabolism and immune checkpoints during ASO, and highlighted how immune checkpoints regulate lipid metabolism to affect ASO. Further exploration of the interactions between lipid metabolism regulators and immune checkpoints may uncover novel potential therapeutic targets for ASO management.